Citalopram Drug Interactions - Kumar V, Dilip; NM, Mahesh; A, Raghunathaguptha (Indian Journal of Pharmacy Practice)
Citalopram is an antidepressant belonging to selective serotonin reuptake inhibitors. Citalopram produces its activity by inhibiting the reuptake of serotonin in the synaptic clefts. So, concomitant administration of drugs (opioids, Monoamino oxidase inhibitors) which are having affect on serotonin or other monoamine levels in the synaptic cleft may produce some adverse effects as a pharmacodynamic interaction. Citalopram is metabolized by CytochromeP450 (CYP) 2C19 and CYP2D6 to desmethylcitalopram and further by CYP3A4 to didesmethylcitalopram. Some drugs may either induce (carbamazepine and rifapicin) or inhibit (buspirone, tramodol, Tricyclic antidepressants) these enzymes and affecting the citalopram levels producing either therapeutic failure or serotonin toxicity. Similarly, citalopram mildly inhibits CYP2C19, CYP2D6 and CYP3A4 and thus affects the plasma levels of the drugs (imipramine, â-blockers, trazodone) which are metabolized by the above enzymes. So, in this review we tried to summarize both the interactions of citalopram with other drugs and other drugs interaction with citalopram and their probable mechanisms which may be helpful for the psychiatrists or physicians to judge the appropriate therapy when the patient is to be co-administered with citalopram.
Keywords: Citalopram; Drug interactions; Pharmacodynamic; Pharmacokinetic